The use of the media as a way to promote oral health: experience of Dentistry academics (Research, Society and Development, 2020)
The present work is an experience report of undergraduate dentistry students at the Federal University of Campina Grande, campus of Patos-Paraíba (PB), participants in the Extension Program (PROBEX) entitled: Human Freshmen - Promoting Oral Health in the Pastoral da Kid. The purpose of this report is to expose the experiences lived on the local community radio, through the dissemination of knowledge about oral health. The program was attended by 18 extension students and 4 coordinating teachers, in addition to students entering the first period of the course and coordinators of the Pastoral da Criança of the Diocese of Patos, Paraíba. The transmission of the program through the radio allows it to have a greater reach of people from different locations, making the knowledge widely disseminated and, in a simple way, information is easily applied, providing these people with a better quality of life. Throughout the term of the Freshmen Human, the program proved to be quite effective, reaching a large number of people and having a positive impact in the municipality of Patos and region.